Psychological Stress and Seborrheic Dermatitis Outcomes: Insights from a Clinical Cohort in Southeast Asia - Brilliant , Fahridho Ramadhana; Biutifasari , Verna; Widjajanto , Hendra; Utami , Prawesty Diah; Adiwinoto, Ronald Pratama (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Seborrheic Dermatitis (DS) is a chronic skin disease that often occurs in areas rich in sebaceous glands, characterized by erythematous patches, plaques, and scales. Psychological factors, especially stress, will affect sebum production and colonization of Malassezia spp being the main cause of seborrheic dermatitis. Stress can increase skin inflammation and worsen DS symptoms. The severity of DS was assessed by the Seborrheic Dermatitis Area Severity Index (SDASI), while stress was measured by the Perceived Stress Scale (PSS). PSS is designed to measure the level of stress in everyday life. SDASI scale used to assess the severity of seborrheic dermatitis. The purpose of the study was to analyze the relationship between the level of stress measured using the Perceived Stress Scale (PSS) with the severity of seborrheic dermatitis evaluated through the Seborrheic Dermatitis Area Severity Index (SDASI). The study involved 51 patients who met the inclusion and exclusion criteria. Data collection was conducted through PSS questionnaires totaling 14 questions and SDASI assessment to measure the severity of DS. The results showed that most patients experienced very severe stress (88.2%) and the severity of severe SDASI (74.5%). The correlation between PSS and SDASI showed a p value of 0.010 (p < 0.05), which showed significant results between the level of stress with the severity of DS with correlation efficiency of 0.359..Stress can worsen the condition of seborrheic dermatitis in which an increase in PSS values is obtained.